Improving Students' Descriptive Text Writing by Using Writing in the Here and Now Strategy at the Tenth Grade Students of Vocational High School - Fitriani, Fitriani; Nur, Rafi Hamdi; Bustamin, Bustamin; Ali, Syahban Mada; Nurisman, Nurisman (Universitas Malikussaleh, 2019)
The objective of the research is to find out whether or not the use of writing in the here and now strategy improve students' ability in writing descriptive text at class X of SMK Negeri 1 Mamuju. The method of this research was quantitative method and type of this research was pre-experimental with one group pre-test, treatment and post-test design. In this research, the researchers took the tenth grade of the second semester in which the total numbers of the population were 323, and the samples consist of 37 students. Based on the data analysis, the alternative hypothesis in this research was accepted because t-test value was more significant than t -table value (11.06 > 1.688). The researchers conclude that Writing in Here and Now strategy can improve the Students' Writing Skill at Tenth Grade Students on the second semester of SMK Negeri 1 Mamuju in academic year 2017/2018.